Dampak Perlindungan Data Pribadi Konsumen dalam Transaksi Online pada Marketplace terhadap Kepuasan Konsumen - Reysha Aurelia Shabilla; Yunesia Amelia Renanta; Sidi Ahyar Wiraguna (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the impact of personal data protection on consumer satisfaction in online transactions in the marketplace. Along with increasing attention to privacy, consumers are increasingly demanding better data protection policies from marketplaces. This research uses a qualitative approach with in-depth interview techniques and content analysis of the privacy policies of several marketplaces in Indonesia. The results show that an effective data protection policy has a positive effect on the level of consumer satisfaction. The main influencing factors are policy transparency, consumer awareness, and their experience with personal data management. However, there is still a gap between existing policies and implementation in the field. Marketplaces that successfully manage personal data well can increase loyalty and competitiveness in an increasingly competitive market. The research also highlights the importance of educating consumers about their rights to personal data and the urgency for marketplaces to improve supervision and compliance with existing regulations. Overall, personal data protection not only fulfills legal obligations, but also becomes a differentiation strategy that increases consumer trust and strengthens marketplaces' position in the market.